APPLICATION OF BLUME METHOD IN FORECASTING RISK ON THE EXAMPLE OF PUBLIC COMPANIES LISTED ON WIG20 - Lisicki, Bartłomiej (Scientific Journal of Bielsko-Biala School of Finance and Law, 2016)
The paper presents the results of studies on the use of Blume’s beta to identify systematic risk of companies listed on the Warsaw Stock Exchange. For this purpose, beta values for WIG20 companies for 2014-2016 were calculated. Weekly rates of return on stocks of certain companies were used in the calculations. Once the annual betas were estimated, the author conducted regression of the results to develop an equation that would enable an estimation of parameters for the future period. In most of the analyzed cases, values of beta parameters calculated on the basis of historical data and the data obtained by Blume’s method were similar. Therefore, Blume’s adjustment method is a good tool for forecasting market risk level of shares of companies listed on the Polish stock exchange.